Expanding the Material Space of Biosustainable Poly(sophorolipids) by Modular Functionalization. Issue 1 (15th October 2018) - Kunde, Tom; Meesorn, Worarin; Weder, Christoph; Börner, Hans G.
Abstract: A general strategy to modify the structurally interesting poly(lactonic sophorolipid) (Poly(LSL)), a polymer derived from the biobased sophorolipid monomer, is presented. Effective backbone modification is achieved via a triazolinedione (TAD)‐ene‐reaction. This enables the straightforward introduction of various functionalities to the double bond in the fatty acid segment of the Poly(LSL). The reaction occurs quantitatively in stoichiometric ratios up to a targeted functionalization degree of 50% and complete functionalization of all double bonds is feasible when three equivalents excess of the TAD moiety with respect to the double bonds are used. It is shown that the thermal and mechanical properties of the modified polymers can be tailored via type and degree of functionalization. The exploited TAD ligation fulfills the criteria of an economic and efficient reaction, making the presented modification strategy straightforward to fine‐tune the material properties and extending the applicability of Poly(LSL) as a material. Abstract : A general strategy to modify poly(lactonic sophorolipid) (Poly(LSL)), which originates from the commonly used sophorolipid biosurfactent as a monomer, is presented. Effective backbone modification is achieved by exploiting the triazolinedione (TAD)‐ene‐reaction. This enables the straightforward introduction of various functionalities regioselectivly to the double bond in the fatty acid segment and opens the material space avaliable for Poly(LSL).